The distribution of public services from the perspective of sustainable spatial equality in the Tabriz Metropolitan in Iran - Zali, Nader; Rahimpoor, Mohammad; Saed Benab, Saeid; Molavi, Mehrnaz; Mohammadpour, Saber (TeMA - Journal of Land Use, Mobility and Environment, 2016)
One of the most prominent consequences of rapid urbanization has recently been the disintegrated distribution of municipal services which predisposes inequality in citizens' benefiting from these services. Therefore, the city planners and managers' main goal must be to achieve the ideal of 'equality of opportunities' to help different groups of urban population have access to public services and eliminate conflicts in the provision of opportunities. In the present descriptive-analytical study, after specifying the indicators, ten regions of Tabriz are ranked in terms of the distribution of municipal services using three different methods (per capita land use, accessibility and residents' idea) and action priorities are presented for each region. The results of this study show that Tabriz has an inappropriate spatial distribution of public services and the population is incompatible with the distribution of services. Region 8 is in a good condition compared to the other while region 7 and 9 has a poor distribution of public services.